2018
DOI: 10.1016/j.autneu.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Challenging cardiac function post-spinal cord injury with dobutamine

Abstract: There is general consensus that spinal cord injuries (SCI) above T6 result in altered sympathetic control of the heart, which negatively influences cardiac structure and function. To by-pass disrupted circuitry and investigate cardiac responses under enhanced sympathetic activity we utilized dobutamine (DOB) stress echocardiography. Animals were divided into a T2, 25g-cm contusive SCI (SCI) or an uninjured control (CON) group. Echocardiography was performed pre-SCI and at 1, 2 and 6weeks post-SCI. Increasing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…; DeVeau et al. ). If rodents, even those with incomplete injuries, experience improvements after that time point, it could have profound implications for individuals living with SCI, especially if the improvements correspond to changes in locomotor behavior or capacity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; DeVeau et al. ). If rodents, even those with incomplete injuries, experience improvements after that time point, it could have profound implications for individuals living with SCI, especially if the improvements correspond to changes in locomotor behavior or capacity.…”
Section: Discussionmentioning
confidence: 97%
“…Dobutamine is a sympathomimetric drug and has been used previously following SCI to increase the chronotrophy and inotrophy of the heart (DeVeau et al. , ; Squair et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have additionally identified a reduction to LV contractile reserve acutely after the injury, which may be attributable to a rapid loss of ‘baseline’ contractility and tonic neuro-hormonal activation of the myocardium that occurs following high-level SCI. Though our group has previously reported that systolic reserve is relatively intact in chronically-injured rats with T2 SCI 13,14 , those observations may reflect chronic hyper-responsiveness of cardiac β-adrenergic receptors 15,16 , which would not have occurred in the acute setting of the current study.…”
Section: Discussionmentioning
confidence: 55%
“…SCI 13,14 , those observations may result from chronic hyperresponsiveness of cardiac β-adrenergic receptors 15,16 , which would not have occurred in the acute setting of the current study. Finally, we found that heart rate was essentially unaltered up to 4 h post-SCI, mirroring data recently reported by our group in Yorkshire pigs 9 .…”
Section: Discussionmentioning
confidence: 75%